2004
DOI: 10.1084/jem.20040520
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Two IκB Kinase-related Kinases in Lipopolysaccharide and Double Stranded RNA Signaling and Viral Infection

Abstract: Viral infection and stimulation with lipopolysaccharide (LPS) or double stranded RNA (dsRNA) induce phosphorylation of interferon (IFN) regulatory factor (IRF)-3 and its translocation to the nucleus, thereby leading to the IFN-β gene induction. Recently, two IκB kinase (IKK)–related kinases, inducible IκB kinase (IKK-i) and TANK-binding kinase 1 (TBK1), were suggested to act as IRF-3 kinases and be involved in IFN-β production in Toll-like receptor (TLR) signaling and viral infection. In this work, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
471
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 531 publications
(492 citation statements)
references
References 47 publications
17
471
2
2
Order By: Relevance
“…77 Fibroblasts or conventional DCs derived from TLR3-deficient mice are capable of producing IFNb following intracellular administration of poly IC and infection with Sendai virus (SeV), Newcastle disease virus (NDV) and VSV. 60,78,79 Together, these observations strongly suggest that host cells express cytoplasmic sensors that can detect actively replicating viruses. In these scenarios, a cytoplasmic protein, namely retinoic acid-inducible gene I (RIG-I), was identified through a functional screening.…”
Section: Recognition Of Viral Components By Non-tlr Sensorsmentioning
confidence: 86%
See 1 more Smart Citation
“…77 Fibroblasts or conventional DCs derived from TLR3-deficient mice are capable of producing IFNb following intracellular administration of poly IC and infection with Sendai virus (SeV), Newcastle disease virus (NDV) and VSV. 60,78,79 Together, these observations strongly suggest that host cells express cytoplasmic sensors that can detect actively replicating viruses. In these scenarios, a cytoplasmic protein, namely retinoic acid-inducible gene I (RIG-I), was identified through a functional screening.…”
Section: Recognition Of Viral Components By Non-tlr Sensorsmentioning
confidence: 86%
“…71 Although it is reported that IRF5 is phosphorylated by TBK1 and IKKi in vitro, cells deficient in TBK1 and IKKi show normal inflammatory responses in response to various TLR ligands. 60,72 As mentioned above, an IRAK1 deficiency does not affect production of inflammatory cytokine. Thus, it is possible that as yet-unknown protein kinases that might associate with MyD88 are responsible for IRF5 phosphorylation and activation.…”
Section: Activation Of Irfs By Tlr7/8 and Tlr9mentioning
confidence: 89%
“…To study the in vivo function of IKK-i and TBK1, relevant knockout mice were generated [37,40]. Deficiency in TBK1 causes TNF-mediated liver degeneration, resulting in embryonic lethality [37].…”
Section: Tbk1 and Ikk-i Activate Irf3 And Irf7mentioning
confidence: 99%
“…However, embryonic fibroblasts were generated from TBK1 K/K mice, stimulated with TLR3 and TLR4 ligands and characterised relative to wild type cells, in relation to IRF3 activation and induction of type I IFNs and IFN-inducible genes. There was severe impairment of the activation and nuclear translocation of IRF3 and induction of IFN-a, IFN-b and IFN-inducible genes, such as RANTES and IP10 (IFN-g-inducible protein 10), in response to both TLR ligands [39,40]. Such defective TLR3 and TLR4 signalling is also evident in bone marrow-derived macrophages derived from TBK1 K/K TNFR1 K/K mice [41], further emphasizing the crucial role of TBK1 in promoting IRF3-dependent gene expression.…”
Section: Tbk1 and Ikk-i Activate Irf3 And Irf7mentioning
confidence: 99%
See 1 more Smart Citation